Contrasts in perception of the interaction between non-native species and climate change - Sam Wenaas Perrin; Carina Lundmark; Camilla Perrin Wenaas; Anders Gravbrøt Finstad (NeoBiota)
Over the last century, intensification of human movement has resulted in a large-scale redistribution of species worldwide. In recent decades, this phenomenon has been further compounded by climate change, creating complex challenges in the management of non-native species. As effective management can be hampered by gaps in communication and understanding between scientific researchers, natural resource managers and the wider public, assessing consensus between these groups is crucial. Here, we adopt an explorative approach to analyse three key groups concerned with the management of freshwater ecosystems – recreational fishers, natural resource managers and scientific researchers. Our objective is to better understand the level of consensus regarding the interaction between non-native species and climate change. We found that, while scientific researchers and managers had varying opinions on the management of non-native species as driven by climate change, recreational fishers were almost unanimously opposed to the potential presence of non-native species, regardless of the nature of their introduction. Additionally, definitions of what constitutes a non-native species varied greatly between and within the groups. Our results underline both the current lack of consensus on the definition and management of non-native species and gaps in understanding between and within the three groups regarding both the nature of non-native species and the range-shifting effects of climate change.